1987
DOI: 10.1128/jvi.61.12.3832-3840.1987
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and termination of duck hepatitis B virus DNA synthesis during virus maturation

Abstract: We characterized a number of important features of the structure of the cohesive overlap region of the DNA genome of duck hepatitis B virus. The 5'-terminal nucleotide of minus-strand DNA was localized to nucleotide 2537, a G residue within the 12-base repeat sequence DR1. This G residue was shown to be the site of a covalent linkage to a protein, consistent with speculation that this protein is the primer of minus-strand synthesis, which occurs by reverse transcription. The 3' terminus of the minus strand was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 34 publications
(61 reference statements)
3
30
0
Order By: Relevance
“…6 to 8), we found that disruption of the identity between r sequences inhibited the template switch. These findings verify the earlier predictions (9,17,25) that the terminal redundancy in minusstrand DNA plays a role in the template switch.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6 to 8), we found that disruption of the identity between r sequences inhibited the template switch. These findings verify the earlier predictions (9,17,25) that the terminal redundancy in minusstrand DNA plays a role in the template switch.…”
Section: Discussionsupporting
confidence: 91%
“…For continuation of plus-strand DNA synthesis, an intramolecular template switch must occur. It has been proposed that the 7-to 9-nucleotide terminal redundancy (called r) facilitates the template switch during synthesis of plus-strand DNA (9,17,25) (Fig. 1, part 7).…”
mentioning
confidence: 99%
“…Examination of the 5' fragments of the two strands generated by EcoRI digestion (Fig. 6c and d) revealed the presence of fragments of the expected sizes for both wild-type and class II mutants (2.54 kb for the minus strand and 0.53 kb for the plus strand), indicating that initiation of both strands occurred at the proper sites (12).…”
Section: Resultsmentioning
confidence: 93%
“…The RNA genome intermediates (pregenomes) are transcribed from a pool of covalently closed circular viral DNA (cccDNA) in the nuclei of infected cells. Reverse transcription takes place in the cytoplasm through a process that uses a combination of template switches (3,14,15,(20)(21)(22)30) to produce relaxed circular double-stranded DNAs, which can be transported to the nucleus to form additional copies of cccDNA (29,32). Progeny cccDNAs retain the precise sequence of the parental cccDNA.We recently reported a second, minor pathway of DNA replication via reverse transcription in the avian hepadnavirus duck hepatitis B virus (DHBV).…”
mentioning
confidence: 99%